What Does Educational Equity Mean? Views of the Harvard Teacher Fellows Program Members - Ferrari, Tarso B. [UNESP]; Bego, Amadeu M. [UNESP]; Rodríguez-Arteche, Iñigo (Springer Nature, 2025)
The 2030 Agenda aims to achieve equitable quality education (EQE), and reform processes in teacher education can play a major role in advancing this goal. Science education research calls for increased efforts to clarify the conceptual dimensions and best pedagogies associated with EQE. The aim of this work is to analyze the views of EQE held by a group of faculties and novice science teachers of the Harvard Teacher Fellows (HTF) program, and its relationship with the formative cohesion of a program that establishes the achievement of EQE as a mission. To this end, the technique Discourse of Collective Subject was employed to access the Core Ideas (CI) held by the participants. The analysis of the interviews yielded five CI on EQE, which could be grouped into ideas related to professional practice, educational goals, and opportunities. These views are aligned with the HTF’s mission and pedagogical principles. However, we argue that other ideas with a more social and political character should have prominence in science teacher education programs.